2017
DOI: 10.1371/journal.pone.0179677
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of Alzheimer's disease associated loci revealed by GWASs

Abstract: Genome-wide association studies (GWASs) discovered a number of SNPs and genes associated with Alzheimer's disease (AD). However, how these SNPs and genes influence the liability to AD is not fully understood. We deployed computational approaches to explore the function and action mechanisms of AD -related SNPs and genes identified by GWASs, including the effects of 195 GWAS lead SNPs and 338 proxy SNPs on miRNAs binding and protein phosphorylation, their RegulomeDB and 3DSNP scores, and gene ontology, pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
4
22
0
2
Order By: Relevance
“…Under other genetic models, rs2333227 SNP slightly elevated the risk of AD. This result was accorded with previous studies [ 31 33 ]. But Combarros and Usui had reported that rs2333227 SNP was not related to AD risk [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…Under other genetic models, rs2333227 SNP slightly elevated the risk of AD. This result was accorded with previous studies [ 31 33 ]. But Combarros and Usui had reported that rs2333227 SNP was not related to AD risk [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…Using genome‐wide association studies (GWASs), Han, Huang, Gao, and Huang () identified functions of the genes and categorized these functions as “regulation of beta‐amyloid formation,” “regulation of neurofibrillary tangle assembly,” “leukocyte‐mediated immunity,” and “protein‐lipid complex assembly” signaling pathways. With the protein–protein interaction network and functional module analyses, they also identified “hub” genes and “bottleneck” genes indicating three subnetworks.…”
Section: Thirteen Among 37 Genes On the Human Ad Genetic Risk Loci Armentioning
confidence: 99%
“…With the protein–protein interaction network and functional module analyses, they also identified “hub” genes and “bottleneck” genes indicating three subnetworks. The hub genes included APOE, PICALM, BIN1, ABCA7, CD2AP, CLU, CR1, MS4A4E, and MS4A6A, while the bottleneck genes included APOE, TOMM40, NME8, PICALM, CD2AP, ZCWPW1, FAM180B, GAB2, and PTK2B (Han et al, ). However, as of 2019, not all genes are well characterized, as indicated by the limited number of publications listed in Table .…”
Section: Thirteen Among 37 Genes On the Human Ad Genetic Risk Loci Armentioning
confidence: 99%
See 1 more Smart Citation
“…Computational analyses represent a starting point to guide the functional research. Our group has previously characterized the GWAS SNPs and genes by computational approaches for osteoporosis [ 3 ], T2D [ 4 ] and Alzheimer's disease [ 5 ]. Here, we used computational approaches to comprehensively analyze obesity GWAS identified SNPs and genes, including functional annotation using RegulomeDB and 3DSNP, effects on miRNAs binding and protein phosphorylation for obesity associated SNPs, and protein-protein interaction network, gene ontology and pathway enrichment analyses for obesity associated genes, in order to identify functional SNPs for follow-up experimental assays, and to provide guidance for future study with regard to the pathogenesis and etiology of obesity.…”
Section: Introductionmentioning
confidence: 99%